Biofilm Forming Antibiotic Resistant Gram-Positive Pathogens Isolated From Surfaces on the International Space Station - Sobisch, Lydia-Yasmin; Rogowski, Katja Marie; Fuchs, Jonathan; Schmieder, Wilhelm; Vaishampayan, Ankita; Oles, Patricia; Novikova, Natalia; Grohmann, Elisabeth (Frontiers in Microbiology, 2019)
The International Space Station (ISS) is a closed habitat in a uniquely extreme and hostile environment. Due to these special conditions, the human microflora can undergo unusual changes and may represent health risks for the crew. To address this problem, we investigated the antimicrobial activity of AGXX®, a novel surface coating consisting of micro-galvanic elements of silver and ruthenium along with examining the activity of a conventional silver coating. The antimicrobial materials were exposed on the ISS for six, 12, and 19 months each at a place frequently visited by the crew. Bacteria that survived on the antimicrobial coatings (AGXX® and silver (Ag)) or the uncoated stainless steel carrier (V2A, control material) were recovered, phylogenetically affiliated and characterized in terms of antibiotic resistance (phenotype and genotype), plasmid content, biofilm formation capacity and antibiotic resistance transferability. On all three materials, surviving bacteria were dominated by Gram-positive bacteria and among those by Staphylococcus, Bacillus and Enterococcus spp. The novel antimicrobial surface coating proved to be highly effective. The conventional Ag coating showed only little antimicrobial activity. Microbial diversity increased with increasing exposure time on all three materials. The number of recovered bacteria decreased significantly from V2A to V2A-Ag to AGXX®. After six months exposure on the ISS no bacteria were recovered from AGXX®, after 12 months nine and after 19 months three isolates were obtained. Most Gram-positive pathogenic isolates were multidrug resistant (resistant to more than three antibiotics). Sulfamethoxazole, erythromycin and ampicillin resistance were most prevalent. An Enterococcus faecalis strain recovered from V2A steel after 12 months exposure exhibited the highest number of resistances (n=9). The most prevalent resistance genes were ermC (erythromycin resistance) and tetK (tetracycline resistance). Average transfer frequency of erythromycin, tetracycline and gentamicin resistance from selected ISS isolates was 10-5 transconjugants/recipient. Most importantly, no serious human pathogens such as methicillin resistant Staphylococcus aureus (MRSA) or vancomycin-resistant Enterococci (VRE) were found on any surface. Thus, the infection risk for the crew is low, especially when antimicrobial surfaces such as AGXX® are applied to surfaces prone to microbial contamination.